Growth Hormone Receptor Regulation in Cancer and Chronic Diseases - Strous, Ger J.; Almeida, Ana Da Silva; Putters, Joyce; Schantl, Julia; Sedek, Magdalena; Slotman, Johan A.; Nespital, Tobias; Hassink, Gerco C.; Mol, Jan A. (Frontiers in Endocrinology, 2020)
The GHR signaling pathway plays important roles in growth, metabolism, cell cycle control, immunity, homeostatic processes, and chemoresistance via both the JAK/STAT and the SRC pathways. Dysregulation of GHR signaling is associated with various diseases and chronic conditions such as acromegaly, cancer, aging, metabolic disease, fibroses, inflammation and autoimmunity. Numerous studies entailing the GHR signaling pathway have been conducted for various cancers. Diverse factors mediate the up- or down-regulation of GHR signaling through post-translational modifications. Of the numerous modifications, ubiquitination and deubiquitination are prominent events. Ubiquitination by E3 ligase attaches ubiquitins to target proteins and induces proteasomal degradation or starts the sequence of events that leads to endocytosis and lysosomal degradation. In this review, we discuss the role of first line effectors that act directly on the GHR at the cell surface including ADAM17, JAK2, SRC, Ubc13/CHIP, proteasome, βTrCP, CK2, STAT5 and SOCS2. Activity of all, except JAK2, SRC and STAT5, act as GHR opponents, rather than team-mates, and counteract GHR signaling. Loss of their function increases the GH-induced signaling in favor of aging and certain chronic diseases, exemplified by increased lung cancer risk in case of a mutation in the SOCS2-GHR interaction site. Insight in their roles in GHR signaling can be applied for cancer and other therapeutic strategies.